Relationship Between Marketing Of Financial Services And Bank Performance In Malaysia : An Empirical Study (1996 - 1998) - Selvan, Perumal (2000)
In modern times, marketing is the backbone of any successful business activity. The present case study seeks to investigate and explore the nexus between marketing efforts and bank performance. The study is based on a sample of 30 commercial banks in Malaysia covering a three year period 1996 to 1998. In addition to empirical analysis, the findings are supported with six interview discussions conducted with bank executives. In this study, the role of marketing activities is related to bank performance in terms of deposits from customers, loans and profits after taxation. In tracing the relationship with deposits, loans and profits, the Pearson’s Correlation Matrix and Simple Linear Regression were used. Our results show a positive correlation between marketing efforts and bank performance. The study suggests that marketing department of each bank should identify and analyse the impact of marketing efforts of their business and deal with the significant factors towards financial and marketing innovation for improving its competitive advantage. For outsourcing there is a wide scope for establishment of a special 'Financial Services Marketing Agency’ through pooled bank resources.